Hypertension in Indonesian air force pilots (Medical Journal of Indonesia, 2012)
Background: To investigate the association between aircraft noise and blood pressure. Methods: A nested case-control study was conducted on Indonesian Air Force pilots doing annual medical check-ups at the Saryanto Institute for Aviation and Aerospace Health (LAKESPRA) from 2003 – 2008. The data extracted from medical records were age, total flight hours, type of aircraft, fasting blood glucose and cholesterol levels, waist circumference, height and weight (Body Mass Index), and blood pressure. Results: There were 549 pilots, 49 were found to be hypertensive, with SBP ≥ 140 mmHg and/or DBP ≥ 90 mmHg. Helicopters pilots were at an almost 2 fold risk of hypertension compared to pilots of the fixed wing aircrafts. Pilots with more than 1400 hours of flight had more than 2 fold risk of being hypertensive compared to those with 1400 flight hours or less. Conclusion: The type of aircraft, which is related to the noise generated, may be a risk factor for developing hypertension in pilots. Increased total flight hours also increased the risk of hypertension. (Med J Indones 2012;21:38-43) Keywords: Aircraft noise, hypertension, pilots